Neutron Discrete Velocity Boltzmann Equation and Its Finite Volume Lattice Boltzmann Scheme (Communications in Computational Physics, 2019)
Simulation of neutron transport process plays an important role in nuclearreactor computation and the numerical technique becomes the focus of nuclear reactorengineering. This paper provides a neutron finite volume lattice Boltzmann method(NFV-LBM) for solving the neutron discrete velocity Boltzmann equation (NDVBE),in which the NDVBE is deduced from the neutron transport equation (NTE) and theNFV-LBM is obtained by integrating the NDVBE. The macroscopic conservation equations recovered from the NDVBE via multi-scale expansion shows that the NDVBEhas higher-order accuracy than diffusion theory, and the numerical solutions of neutron transport problems reveal the flexibility and applicability of NFV-LBM. This papermay provide some alternative perspectives for solving the NTE and some new ideasfor researching the relationship between the NTE and other approximations.
Keywords: Neutron transport; neutron discrete velocity Boltzmann equation; neutron finite volume lattice Boltzmann; diffusion theory.